Improving Mathematics Learning Outcomes Using Multiplication Bag Media for Grade IV Elementary School Students. - Zainul Umam Zainul Umam; Nabilatus Sholihah; Raysa Eka Delvira; Eriq Ilham Surya Novanta; Machful Indrakurniawan (Literasi Nusantara, 2026)
This study aims to improve mathematics learning outcomes through multiplication pocket media among fourth-grade students at SDN Katol Barat 1 Bangkalan. Employing Classroom Action Research (CAR) across two cycles, this research involved 24 fourth-grade students as subjects. Data collection methods included interviews, tests, observations, and documentation, which were analyzed using both quantitative and qualitative approaches. The findings reveal that the integration of multiplication pocket media significantly enhances student achievements. In the pre-cycle stage, only [37.46%] of students achieved the learning mastery criteria (KKTP). Following the intervention, the student passing rate increased to [48.13%] in Cycle I, and further escalated to [74,58%] in Cycle II. Additionally, the concrete media boosts students' classroom engagement and enthusiasm. This study concludes that multiplication pocket media serves as an effective instructional tool to optimize elementary mathematics learning outcomes.